Sistem Kendali Otomatisasi Suhu Kelembaban dan Pencahayaan Pada Terrarium Berbasis Internet of Things - Yoastha, Qano Triez; Nirmala, Irma; Suhardi, Suhardi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Terrarium is one of the interesting and environmentally friendly room decorative solutions. However, the owner must be more careful to pay attention to the optimal humidity and light conditions for the terrarium. In an effort to overcome these obstacles, this research makes an Internet of Things (IoT)-based automation control system for terrarium watering and lighting. The system is equipped with a humidity sensor (DHT22) and a light intensity sensor (Light Dependent Resistor) to detect environmental conditions. When abnormal humidity is detected, the system will automatically water the plants, while the lights will be adjusted to the light intensity of the room. In addition, the system data is presented in real-time through the website and displayed on the LCD screen. The test results show the accuracy rate of the humidity sensor is 97.45% and the light intensity sensor is 98.51%, while the ultrasonic proximity sensor has an average accuracy of about 98.61%. This research offers a practical solution for maintaining terrariums efficiently and effectively through the application of IoT technology.